The Impact of the Black Lives Matter Movement on American Society: The Rebirth of African American Activism - Ms. Manar Benyettou, DR.Youcef bennaa (université mohamed boudiaf .m'sila, 2023)
Abstract This abstract provides an overview of the Black Lives Matter (BLM) movement, its aims and objectives, the methods employed, the findings, and a concluding remark regarding its sociopolitical impact and influence on policing reforms. The Black Lives Matter (BLM) movement emerged as a response to ongoing social discrimination and police brutality faced by Black individuals in the United States, gaining significant national and international attention. The primary aim of the BLM movement is to advocate for social reform, equality, and an end to social discrimination and police violence against Black citizens. It seeks to raise awareness, mobilize communities, and press for changes in policing policies and practices. The BLM movement initially gained momentum through the use of social media platforms, particularly the hashtag #Black Lives Matter. It organized peaceful demonstrations, protests, and rallies across various states and countries to highlight the urgent need for systemic change. The BLM movement has sparked a considerable debate due to its controversial aspects, including episodes of violence, property damage, and clashes with law enforcement. However, it has also successfully influenced major police reforms, such as police department defunding and the implementation of laws aiming to address excessive use of force. While the Black Lives Matter movement has faced criticism for its destructive elements, it has undeniably played a significant role in driving public awareness and pushing for reforms in policing practices. The movement has highlighted the urgent need for social justice and equality, calling for continued efforts to address systemic racism and ensure fair treatment for all individuals, regardless of their race or ethnicity
Keywords: Key Words BLACK LIVES MATTER, DISCRIMINATION, RACISM, POLICE VIOLENCE.